SELEÇÃO DE ISOLADOS DE TRICHODERMA DO MATO GROSSO DO SUL PARA O BIOCONTROLE DE MACROPHOMINA PHASEOLINA - Idelfonso Oliveira , Thalita; Fernandes da Costa , Brenda; de Souza da Silva, Talísia; André Sganzerla Graichen , Felipe (ANAIS DO ENIC, 2026)
-